1862 Conn. Acts 76, An Act In Addition To “An Act to Provide For the Organization And Equipment Of A Volunteer Militia, And To Provide For the Public Defense,” chap. 68, § 34 - (:unkn) unknown (General Publisher, 1862)
Required brigade inspectors to annual inspect armories and gun houses of the companies belonging to their brigades. Inspectors shall also inspect the rooms occupied by regimental bands.
--
Keywords: ARMED FORCES